2015
DOI: 10.5395/rde.2015.40.1.30
|View full text |Cite
|
Sign up to set email alerts
|

A study on the compatibility between one-bottle dentin adhesives and composite resins using micro-shear bond strength

Abstract: ObjectivesThis study was performed to determine whether the combined use of one-bottle self-etch adhesives and composite resins from same manufacturers have better bond strengths than combinations of adhesive and resins from different manufacturers.Materials and Methods25 experimental micro-shear bond test groups were made from combinations of five dentin adhesives and five composite resins with extracted human molars stored in saline for 24 hr. Testing was performed using the wire-loop method and a universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…However, the reproducibility of testing results is affected by various factors regarding the inherent weakness of test institute [3]. Although ISO 11405 [23] strictly stresses that "a limitation of the bonding area is important," in most μ-SBS tests, the step of restricting the area of both the adhesive and the resin was often ignored [22,[24][25][26][27], and only the area of the resin cylinder was taken as the bonding area to calculate the bond strength of tested materials. Therefore, the objective of this study was to compare the bond quality of different adhesive systems by employing the μ-SBS test with and without adhesive area restriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reproducibility of testing results is affected by various factors regarding the inherent weakness of test institute [3]. Although ISO 11405 [23] strictly stresses that "a limitation of the bonding area is important," in most μ-SBS tests, the step of restricting the area of both the adhesive and the resin was often ignored [22,[24][25][26][27], and only the area of the resin cylinder was taken as the bonding area to calculate the bond strength of tested materials. Therefore, the objective of this study was to compare the bond quality of different adhesive systems by employing the μ-SBS test with and without adhesive area restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The etch-and-rinse adhesive system and the self-adhesive system are the most frequently employed in clinical works [20]. Before new adhesive materials can be put into clinical use, it must be evaluated through various laboratory methodologies; one such methodology is the μ-SBS test, which is one of the most essential tests for predicting the efficiency of new adhesives [20][21][22]. However, the reproducibility of testing results is affected by various factors regarding the inherent weakness of test institute [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies reported the dentin bond strengths of various all-in-one adhesives on the market [7][8][9][10][11] ; however, most studies combined adhesive systems with accompanying resin composites. By contrast, the compatibility of resin composites with the different manufacturer's adhesive systems in terms of the dentin bond strength has not reached a consensus in previous studies [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…However, a clear protocol of EDC dentin surface coating is still questionable [ 22 , 23 ]. Little attention has been focused on investigating the influence of EDC on the dentin shear bond strength, one of the most essential, valuable and reliable characteristics for initial screening of new dental adhesive systems [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%